PATIENT CLIENT CONSUMER BEHAVIOR IN PHYSICAL AND ONLINE PHARMACIES. A COMPARATIVE ANALYSIS OF PHARMACEUTICAL CARE AND ARTIFICIAL INTELLIGENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study highlights distinct consumer behaviors in physical versus online pharmacies, revealing critical insights into the evolving landscape of pharmaceutical care. Findings indicate that online pharmacy users are more likely to make impulsive purchasing decisions driven by promotional offers, spending an average of only 50 seconds on websites. In contrast, consumers in physical pharmacies engage in more deliberate decision-making, heavily influenced by personal interactions with pharmacists. The implications of these findings suggest that consumer behavior in the pharmaceutical sector is significantly shaped by the purchasing environment. The integration of artificial intelligence (AI) in online pharmacies enhances operational efficiencies and personalization but raises concerns regarding the loss of human interaction and emotional intelligence, both crucial for building trust. This highlights the need for further research into balancing technology and personal care in e-health environments. From a practical standpoint, pharmacies must adapt to these evolving consumer preferences by adopting hybrid models that leverage the strengths of both physical and online settings. This includes enhancing the online shopping experience through personalized AI-driven recommendations while maintaining robust patient-pharmacist interactions in physical locations. Implementing tele pharmacy services can bridge the gap, facilitating access to pharmacist consultations without sacrificing personal connection. Ultimately, the study emphasizes the necessity for pharmacies to prioritize the human elements of care that foster trust and loyalty among patients, especially as the industry increasingly incorporates digital solutions. By doing so, pharmacies can improve patient satisfaction and adherence while ensuring a competitive advantage in a rapidly changing healthcare landscape. These insights are vital for pharmacy practitioners, healthcare policymakers, and researchers navigating the complexities of consumer behavior in the digital age.